Functional Local Renin-Angiotensin System in Human and Rat Periodontal Tissue - Santos, Carlos F.; Morandini, Ana C.; Dionisio, Thiago J.; Faria, Flavio A.; Lima, Marta C.; Figueiredo, Caio M.; Colombini-Ishikiriama, Bella L.; Sipert, Carla R.; Maciel, Rubens P.; Akashi, Ana P.; Souza, Gabriela P.; Garlet, Gustavo P.; et al. (Public Library Science, 2015)
The initiation or progression of periodontitis might involve a local renin-angiotensin system (RAS) in periodontal tissue. The aim of this study was to further characterize the local RAS in human and rat periodontal tissues between healthy and periodontally-affected tissue. Components of the RAS were investigated using in vitro, ex vivo and in vivo experiments involving both human and Wistar rat periodontium. Although not upregulated when challenged with P. gingivalis-lipopolysaccharide, human gingival and periodontal ligament fibroblasts expressed RAS components. Likewise, healthy and inflamed human gingiva expressed RAS components, some of which were shown to be functional, yet no differences in expression were found between healthy and diseased gingiva. However, in inflamed tissue the immunoreactivity was greater for the AT(1)R compared to AT(2)R in fibroblasts. When compared to healthy tissue, ACE activity was increased in human gingiva from volunteers with gingivitis. Human-gingiva homogenates generated Ang II, Ang 1-9 and Ang 1-7 when incubated with precursors. In gingiva homogenates, Ang II formation from Ang I was nearly abolished only when captopril and chymostatin were combined. Ang 1-7 formation was significantly greater when human gingiva homogenates were incubated with chymostatin alone compared to incubation without any inhibitor, only captopril, or captopril and chymostatin. In rat gingiva, RAS components were also found; their expression was not different between healthy and experimentally induced periodontitis (EP) groups. However, renin inhibition (aliskiren) and an AT(1)R antagonist (losartan) significantly blocked EP-alveolar-bone loss in rats. Collectively, these data are consistent with the hypothesis that a local RAS system is not only present but is also functional in both human and rat periodontal tissue. Furthermore, blocking AT(1)R and renin can significantly prevent periodontal bone loss induced by EP in rats.